A study to assess the knowledge and attitude towards HIV of pharmacy students from Mumbai university - Thingore, Chetan; Joshi, Ruchira; Kshirsagar, Viplav; Limaye, Dnyanesh (International Journal Of Community Medicine And Public Health, 2020)
Background: India is the biggest HIV epidemic in the world. The role of a pharmacist is pivotal in educating the general masses. The aim of the study was to determine the knowledge and attitude of pharmacy students from University of Mumbai. Methods: A cross-sectional study was conducted in University of Mumbai during February-March 2020. Therein, 307 students (214: females and 94: males) participated in the study. The questionnaire was distributed in the classroom and data was collected by means of Google-forms. Furthermore, the data was analysed using IBM SPSS version 23. Results: The participants demonstrated good knowledge (84%) and attitude (76%) score. With respect to knowledge score, no significant difference was observed except for responses of two questions, aim of the antiretroviral therapy (ART) and Avoidance of sexual intercourse can decrease the risk of HIV. With respect to attitude score, Volunteering to work at an institute for the welfare of HIV patients showed a significant difference. Conclusion: The current study showed that there were no misconceptions or negative attitude regarding HIV among the students. However, a study with greater sample size must be conducted across India for further investigation.